Integrating cognitive processing therapy for posttraumatic stress disorder with cognitive behavioral therapy for eating disorders in PROJECT RECOVER. Issue 3 (4th May 2021) - Trottier, Kathryn; Monson, Candice M.
ABSTRACT: Posttraumatic stress disorder (PTSD) frequently co-occurs with eating disorders (ED) and is likely to be a powerful ED maintaining factor for a significant subgroup of individuals. The goal of PROJECT RECOVER is to develop and evaluate concurrent integrated treatment approaches for ED-PTSD to enable these individuals to recover from both their ED and PTSD. To date, we have trialed two approaches to concurrent/integrated treatment in PROJECT RECOVER: (1) concurrent delivery of Cognitive Processing Therapy (CPT) for PTSD to individuals receiving intensive ED treatment, and (2) delivery of a manualized individual cognitive-behavioral therapy (CBT) addressing both ED and PTSD (Integrated CBT for ED-PTSD) following a period of initial ED treatment. Interventions from both CBT for ED, and CPT for PTSD can be utilized and adapted to address the functional relationship between ED and PTSD, and promote full recovery from both disorders. Examples include integrating PTSD symptoms into the cognitive-behavioral individualized formulation of ED maintenance; integrating the ED into psychoeducation about PTSD maintenance; and identifying maladaptive beliefs that connect the ED to the trauma and/or PTSD. Emerging evidence suggests that CPT can be successfully integrated with CBT for ED.